The Homotopy Analysis Method for Solving Multi- Fractional Order Integro-Differential Equations - Hanan, Ibtisam K (Al-Nahrain Journal of Science, 2011)
Abstract: In this paper we use the homotopy analysis method to solve special types of the initial value problems that consist of multi-fractional order integro differential equation in which the fractional derivative and fractional integral in them are described in the Caputo sense and Riemann-Liouville sense respectively. Numerical examples are solved by using this method. These examples shows that high accuracy, simplicity and efficiency of this method.